EPIDEMIOLOGI DAN DETERMINAN SOSIAL STUNTING DI PROVINSI KEPULAUAN: TINJAUAN LITERATUR FAKTOR RISIKO DAN EFEKTIVITAS INTERVENSI MULTISEKTORAL PADA BALITA DI NUSA TENGGARA BARAT - Sunanto Sunanto; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Background: Stunting is a manifestation of chronic malnutrition that impacts the quality of human resources, especially in regions with island geographical characteristics such as West Nusa Tenggara (NTB). Although interventions have been implemented, stunting prevalence in this region still requires in-depth analysis regarding social determinants and the effectiveness of cross-sectoral coordination. Objective: This study aims to map the epidemiological profile, identify dominant social determinants, and evaluate the effectiveness of multisectoral interventions in NTB Province through a literature review. Methods: This research employed the Systematic Literature Review (SLR) method. Article searches were conducted on Scopus and Google Scholar databases within the 2014-2024 timeframe. Article selection followed strict inclusion and exclusion criteria, resulting in 10 primary articles analyzed qualitatively. Results: Findings indicate that social determinants such as access to sanitation (WASH), maternal education level, and family economic status are the primary risk factors in NTB. The island region's characteristics cause significant disparities in food access and health services. Specific interventions (medical) proved effective when supported by sensitive interventions (non-medical) through multisectoral collaboration and local volunteer empowerment. Conclusion: Stunting management in NTB requires a region-based approach that is adaptive to the geographical constraints of the islands. Policy synchronization between central and local governments, along with the strengthening of basic infrastructure, is key to accelerating stunting reduction.